Analisis Yuridis Prosedur Penggunaan dan Pertanggungjawaban Pengalokasian Dana Bantuan Operasional Sekolah (BOS) Tingkat Sekolah Dasar di Kota Serang - Maajid Risnanditya Purwatama; Muhammad Fasyehuddin; Nurikah (Epistemik: Indonesian Journal of Social and Political Science, 2021)
Article 31 of the 1945 Constitution mandates that the government is able to guarantee the provision of education for every citizen. To realize this mandate, the government organized a school operational assistance fund program regulated in the Regulation of the Minister of Education and Culture Number 18 of 2019. The research aims to discuss the use and accountability of the School Operational Assistance program at the elementary school level in Serang City, as well as the constraints in its implementation. The School Operational Assistance Program (BOS). This research uses juridical empirical research methods, as well as library data, and analysis in qualitative form. The results showed that the use of BOS funds in elementary schools in Serang City was focused on developing libraries, purchasing books, developing non-textbooks, admitting new students, learning and extra-curricular students, evaluating learning, school management, developing teacher professional, education personnel. as well as school management, subscriptions to resources and services, maintenance of school facilities and infrastructure, honoraria, and maintenance of multi- media learning tools. The form of school accountability for school operational assistance funds is in the form of submitting reports on the realization of the use of BOS funds through bos.kemdikbud.go.id. The obstacles in the implementation of the BOS Program are the insufficient transparency of the school against parents and students, and there are still some things that are not right on target in the management and distribution of School Operational Assistance Funds.